TR Jets above Magnetic X-Type Null Points - Ehsan Tavabi; Mehri Heidari; Azam Mollatayefeh (Iranian Journal of Astronomy and Astrophysics)
Various chromosphere and transition region jet-like structures abound playing an essential role in the dynamics and evolution therein. Tentatively identifying the wave characteristics and oscillatory behavior in the outer solar atmosphere helps to understand this layer better. In addition to the whip-like behavior, null-point motions in the reconnection site can excite transversal oscillation along the magnetical dense Jets, which is called the kink mode wave, and also this mode can evolve into Alfven wave after its propagation into the more homogeneous medium. The study of X-ray jets is an important topic in understanding the heating of the solar corona and the origin of the fast wind. The recently launched Hinode mission permitted us to observe the excellent proxies of these jets with an unprecedented high spatial resolution of 120 km on the Sun. We selected a high cadence sequence of SOT (Hinode) observations taken with both the HCaII and the Halpha filter to look at the details of the dynamics revealed by a significant jet event. Both wavelet and amplitude spectra analysis were used to analyze the observed kink wave and the time variations of intensities during the event. The results are discussed in the frame of different models implying reconnections with the inference of the dynamical phenomena occurring near several null points, including the oscillatory behavior.